[P150] Air density dependence of the response of the PTW sourcecheck 4PI ionization chamber to PD-103 brachytherapy sources. (August 2018) - Rodriguez, Cristina Forastero; Montes, Joaquín; del Río, Julia Torres; Jiménez-Melguizo, Miguel; Jóver, Clara; Guirado, Damián; Tornero-López, Ana M.; Pérez-Calatayud, José; Lallena, Antonio M.
Abstract : Purpose: Some well-type ionization chambers, when used for low-energy radionuclides, show a residual dependence on the air density once the standard pressure and temperature factor is applied.In this work the response of the PTW SourceCheck 4Pi ionization chamber to Pd-103 sources is analysed as a function of the air density, for the first time.Also an additional study for the Standard Imaging HDR1000 Plus chamber is performed. Methods: Three PTW SourceCheck 4Pi TW33005 (with a PTW Unidos electrometer), and a Standard Imaging HDR1000Plus (with a Standard Imaging MAX4000 electrometer) were introduced individually in a homemade pressure chamber equipped with a thermometer-hygrometer-barometer THB 40 (PCE Instruments).Different air densities were obtained by changing the pressure inside the chamber by means of a vacuum pump.Four TheraSeed® 200 Palladium-103 seeds (Theragenics Corporation) were used. Raw measurements must be corrected according to: M corr = g 0 ( ρ ) g 1 ( ρ ) M raw, (1). where g 0 ( ρ ) is the usual temperature-pressure correction factor and g 1 ( ρ ) an additional factor verifying: g 0 ( ρ ) g 1 ( ρ ) = ρ / ρ 0 - u, (2). with ρ and ρ 0 the air density under actual and standard conditions, respectively, and u a parameter to be fitted. To study the influence of the experimental setup geometry and the number of seeds, an adapter with four seeds separated from each other by spacers commonly used in prostate implants was used. Results: SourceCheck 4Pi and HDR1000Plus chambers show a potential dependence with the air density, with u  = 0.533 ± 0.002 (k = 2) for the former and 0.431 ± 0.003 (k = 2) for the latter. The responses of the three SourceCheck 4Pi chambers were the same, within the uncertainties.Besides, no influence with the number of seeds simultaneously measured was observed. Conclusions: Once corrected for the usual temperature-pressure factor, the PTW SourceCheck 4Pi chamber shows a residual dependence on the air density for Pd-103 sources that is better described by a potential function than by a linear one, contrary to what happens when using I-125 sources. The reason for these differences is currently being investigated using Monte Carlo simulation techniques. The result for HDR1000 Plus differs by 1.6% with those obtained by Griffin et al. (2005).